Edukasi dan Pembuatan Produk Eco Enzyme dari Limbah Kulit Jeruk di Kelurahan Limau Manis Kota Padang - Purnawan Pontana Putra; Salman Salman; Rustini Rustini (Warta Pengabdian Andalas, 2023)
Eco Enzymes can accelerate biochemical reactions to produce enzymes that break down fruit or vegetable waste. It was from this waste is one way of waste management that utilizes kitchen scraps to produce beneficial liquids. Community service was conducted in the Limau Manis Village of Padang City. Pre-tests and post-tests in the form of questions were conducted to assess the community's understanding of the Eco Enzyme material provided. Educational materials about the theory and importance of the Eco Enzyme product were provided by a lecturer in Pharmaceutical Chemistry from the Faculty of Pharmacy at Universitas Andalas regarding its uses and the products that can be sold. The theory material was made into a booklet and given to participants to take home and read again. Direct practice was conducted on making Eco Enzyme from orange peel waste obtained from fruit sellers. The T-Test results obtained a t-value of -5.047 with a p-value of 0.0001 (smaller than the alpha of 0.05). This value shows that this community service activity significantly improves the community's understanding of Eco Enzyme. In the future, an Eco Enzyme product in the form of a liquid that can be used will be obtained.